The Impact of Environmental Performance on Corporate Profitability: Evidence from South African Publicly Listed Metal & Mining Companies - Tattersall, Kyle Ross (The IIE, 2020)
Empirical results of more than three decades of research concerning the link between environmental performance and firm financial performance remain inconclusive. Existing literature has so far neglected the multifaceted nature of both performance meta-constructs, giving rise to the prevailing fragmentation in contemporary findings. Using a sample of 12 large capitalization South African metal and mining firms listed on the Johannesburg Stock Exchange, this paper investigates the effect of environmental performance on firm financial performance. Panel data analysis – employing multi-regression techniques – was performed between the years 2015 and 2020 using secondary data obtained from publicly available ESG reports and audited financial statements concerning respective industrial metal and mining industry constituents. Firstly, a significant positive correlation was found to exist between ESG scores and Return on Assets. Secondly, a significant negative correlation was found to exist between ESG scores and Tobin’s Q. Evidence of such financial gain with respect to environmental performance, provides impetus for firms and managers seeking to implement sustainable practices. These results demonstrate that it does pay to be green.
Keywords: Environmental performance; Financial performance; Return on assets; Sustainability; Tobin's Q